A Novel Practical Fixed-Time Speed Control of Permanent Magnet Synchronous Motors with Input Saturation - Varin Cholahan; Napasool Wongvanich; Worapong Tangsrirat (My University, 2025)
In this article, we focus on a control problem for the speed control of a permanent magnet synchronous motor (PMSM). An antisaturation adaptive fixed-time nonsingular sliding mode control (AFFTNSM) with disturbance estimation compensation is designed for a class of second-order nonlinear systems to improve PMSM system performance. Firstly, a novel fast fixed-time nonsingular sliding mode surface is chosen based on the error dynamic equation. Then, a practical fixed-time sliding mode control algorithm is proposed where the stability of the proposed controller is demonstrated to show the convergence of the velocity tracking error to a neighborhood of the origin in fixed-time. The implementation of feedforward compensation of disturbance enhances the dynamic performance of the fast fixed-time nonsingular sliding mode control rule, resulting in reduced chattering phenomena. Numerical simulation results are provided to verify the efficiency of the proposed method.
Keywords: Sensorless Control of Electric Motors; Electric Motor Design and Analysis; Multilevel Inverters and Converters